Acceptability and use of an online health priorities self-identification tool for older adults: A qualitative investigation - Mroz, Emily L.; Hernandez-Bigos, Kizzy; Esterson, Jessica; Kiwak, Eliza; Naik, Aanand; Tinetti, Mary E. (PEC innovation, 2023)
To examine the use of a web-based, self-directed health priorities identification tool for older adults with multiple chronic conditions (MCCs). We recruited a gender- and racially-diverse, highly educated sample of older adults with MCCs to engage with our My Health Priorities tool, then complete a semi-structured interview. Thematic analysis was used to examine interview transcripts. Twenty-one participants shared perspectives on the acceptability and use of the tool. Three themes (with eleven subthemes) were generated to describe: website user experience feedback, the content of the health priorities identification process, and the tool's capacity to empower communication and decision making. Participants found this tool acceptable and easy to use, describing a variety of benefits of the priorities self-identification process and offered suggestions for refinement and broader implementation. Older adults with limited internet navigation abilities or misconceptions about the self-directed process may benefit from clinicians clarifying the purpose of the process or initiating priorities-aligned discussions. This novel tool can help older adults with MCCs define what matters most for their health and healthcare, informing a variety of health decisions. This tool may enable and motivate patients to lead health priorities decision-making discussions with clinicians and care partners. •Older adults with multiple chronic conditions benefit from identifying health priorities.•A web-based tool supported self-identification of health priorities.•Users felt empowered to engage in priorities-aligned discussions with clinicians and family.•Users identified structural and content refinements that may improve usability.